Willingness to perform bystander CPR before and after the BLS AED course - Bartczak, Maria; Balcerzyk-Barzdo, Elżbieta (Polish Journal of Public Health, 2011)
Introduction. Almost 60% of adult deaths connected with ischemic heart disease are out-of-hospital deaths, and the leading cause of death is sudden cardiac arrest (SCA) in ventricular fibrillation mechanism. Prompt activation of the ambulance service and immediate bystander cardiopulmonary resuscitation (CPR) have great influence on the success of resuscitation efforts and improve the chances of victims’ survival. Aim. The aim of this study was to determine the willingness to perform bystander CPR by the participants of the BLS AED courses, before and after the training. Moreover, researchers wanted get to know the reasons why the participants take part in such trainings. Researchers also wanted to find any possible correlation between age, sex, marital status, education and willingness to perform bystander CPR both before and after the course. Material and methods. The survey was conducted among the 203 participants who took part in the BLS AED courses. The questionnaires contained questions about basic sociometric issues, reasons for taking part in the training and willingness to perform bystander CPR before and after the course, were distributed after the training. One hundred and fourteen women and 89 men took part in the survey. Results. Bystander CPR would not be performed by 52.2% of the participants before the course. However, after the course, 96.1% of the participants declared that their first aid knowledge was good enough to provide a person in sudden cardiac arrest with help. Conclusion. Willingness to perform bystander CPR before the BLS AED course is low. Women less frequently declare their willingness to provide frst aid before the course. Taking part in such training visibly increases the chances of rendering first aid by the participants. Work-related but also personal issues were the main causes of taking part in BLS AED course. It is necessary to prepare more first aid courses in order to increase willingness to perform bystander CPR, and thus increase the chances of survival of victims in out-of-hospital cardiac arrest.